Perception, hallucination, and illusion - Fish, William, 1972- (Oxford : Oxford University Press, 2009)
A treatment of disjunctivism about visual experiences in the service of defending a naive realist theory of veridical visual perception, this book includes detailed theories of hallucination and illusion that show how such states can be indistinguishable from veridical experiences without sharing any common character.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Visual perception; Perception (Philosophy); Hallucinations and illusions